(untitled) (Annals of Medical Research, 2025)
Aim: This study investigated the effect of lung involvement in Rheumatoid Arthritis (RA) on sarcopenia. Materials and Methods: A retrospective analysis was conducted on patients with RA diagnosed between January 2020 and January 2024. Patients with non-contrast thoracic CT scans available in the hospital database were included. A control group consisting of individuals without any inflammatory diseases was also selected. Muscle area (MA) and muscle-to-aorta density (M/A density) ratio were compared between the RA and control groups, as well as between RA patients with and without pulmonary involvement. Results: A total of 187 individuals (156 women, 31 men) were included in the study, comprising 84 patients in the RA group and 103 in the control group. The M/A density ratio was significantly lower in the RA group (p<0.001). Among RA patients, 30 (36%) had pulmonary involvement. The M/A density ratio was significantly lower in RA patients with lung involvement compared to those without (p = 0.016). However, the muscle area showed no significant difference among the groups (p = 0.683). Conclusion: This study found that RA lung involvement may be associated with increased muscle adiposity. Prospective studies with large populations are needed to confirm this association.